Faktor-Faktor Yang Mempengaruhi Penundaan Proses Klaim JHT BPJS Ketenagakerjaan Cabang Medan - Oktapianti, Wanda Aulia; Dwi Melisa Putri; Nabila Wulandari; Restu Amalia Mazid; Sri Hajijah Purba (Journal of Educational Innovation and Public Health, 2024)
This study aims to identify the factors influencing delays in the claim process of theRetirement Savings Scheme (JHT) at the BPJS Employment Branch Office in Medan. Aqualitative approach was employed through in-depth interviews with BPJS employees,rticipants,andbranch managers.The findingsrevealthatinternalfactorssuch asincomplete documentation, human resource limitations, and technological system disruptionsplay a significant role in causing claim delays. Additionally, external factors includingsuddengovernmentregulatorychangesand inadequateparticipantinformation alsocontribute to these delays. The impact of claim delays on participant satisfaction is profound,necessitating improvements in claim management administration. Based on these findings, itis recommended to enhanceparticipant education and awareness, strengthen humanresources, improve technological system reliability, and develop adaptive mechanisms forregulatory changes to enhance efficiency and participant satisfaction in the JHT claimprocessattheBPJS EmploymentBranchOfficein Medan